Haseena maan jayegi - Mehra, Prakash; Bhooshan, Indu; Kalyanji Anandji (Musical group); Ultra Video (Firm) (Mumbai : Moser Baer Entertainment, 2009)
Kamal and Archana are in love with each other and got married. Shortly after their marriage, Kamal is called to the front as war has broken out. While preparing for war be meets with Rakesh his look-alike. Rakesh plans to kill Kamal and take his place with the beautiful Archana, but Kamal will not have him have his way, both fight and eventually Kamal emerges as the winner. He runs from the front and goes home to his wife, Archana who is happy to see him back. Army personnel think Rakesh has become a deserter and also think that Kamal is missing in action and believed dead. The army personnel notify Archana, who is thrown in a dilemma, is it Rakesh or Kamal that she has been spending time with?
Copyright notice on disc: Ultra Video.
Originally released theatrically in 1968.
Summary taken from container.
Not viewed.
Sources used: videodisc container; cataloging record from OvOp field office.
Music, Kalyanji Anandji.
Keywords: Murder -- Drama; Lookalikes -- Drama; Fiction films